PENERAPAN HOME VISIT DENGAN STRATEGI CONTROLLED HOME LEARNING PADA SISWA RA MIFTAHUL ULUM KEPANJEN JEMBER - Fina Aunul Kafi; Dewi Latifah Yuniarti (Universitas Wahid Hasyim Semarang, 2021)
The impact of the Covid-19 pandemic makes the Minister of Education and Culture of the Republic of Indonesia since March 2020 stipulates that learning to be carried out at home for all levels of education, including kindergarten. RA Miftahul Ulum Kepanjen Jember is the affected part of this policy. There are many problems faced by students and parents of RA Miftahul Ulum during the online learning process, such as absent learning interactions, low motivation, and parents do not know how to operate online learning applications. The researcher conductes community service by cooperating with RA Miftahul Ulum as a partner in implementing the home visit learning model with a controlled home learning strategy. This community service article aimed to describe home visits with controlled home learning strategies and the response of students and parents of RA Miftahul Ulum students. The research method used was a qualitative method with data collection techniques using a questionnaire involving respondents 40 parents and 40 students. The results showed that on average the students and their parents responded positively to the home visit with a controlled home learning strategy that was applied to learn at home. In conclusion, the teacher visit learning model with a controlled home learning strategy can improve the learning quality of RA Miftahul Ulum students as long as distance learning is established by the government. Keywords: home visit, motivation, controlled home learning, online, offline AbstrakDampak pandemi Covid-19 membuat Menteri Pendidikan dan Kebudayaan RI sejak Maret 2020 menetapkan agar pembelajaran dilakukan di rumah secara daring untuk semua jenjang pendidikan, termasuk taman kanak-kanak. RA Miftahul Ulum Kepanjen Jember menjadi bagian yang terimbas kebijakan tersebut. Banyak masalah yang dihadapi siswa dan orangtua RA Miftahul Ulum selama proses belajar daring, seperti tidak adanya interaksi belajar, motivasi belajar rendah, dan tidak semua orangtua tahu cara mengoperasikan aplikasi pembelajaran daring. Peneliti melakukan pengabdian masyarakat dengan menggandeng RA Miftahul Ulum sebagai mitra dalam menerapkan model pembelajaran home visit dengan strategi controlled home learning. Artikel pengabdian masyarakat ini bertujuan untuk mendeskripsikan home visit dengan strategi controled home learning dan respon siswa dan orangtua RA Miftahul Ulum. Metode penelitian yang digunakan adalah metode kualitatif dengan teknik pengumpulan data menggunakan kuesioner yang melibatkan responden 40 orangtua dan 40 siswa. Hasil penelitian menunjukkan rata-rata siswa dan orangtua merespon positif home visit dengan strategi controlled home learning yang diterapkan untuk pembelajaran di rumah. Kesimpulannya, model pembelajaran kunjungan guru dengan strategi controlled home learning dapat meningkatkan kualitas pembelajaran siswa RA Miftahul Ulum selama ditetapkannya pembelajaran jarak jauh oleh pemerintah.Kata kunci: home visit, motivasi, controlled home learning, daring, luring